Interaction Between Slow Wave Sleep and Obstructive Sleep Apnea in Prevalent Hypertension. Issue 2 (February 2020) - Ren, Rong; Covassin, Naima; Zhang, Ye; Lei, Fei; Yang, Linghui; Zhou, Junying; Tan, Lu; Li, Taomei; Li, Yun; Shi, Jie; Lu, Lin; Somers, Virend K.; et al.
Abstract : Due to frequent abnormal breathing events and their effects on sleep architecture, patients with obstructive sleep apnea (OSA) exhibit decreased amounts of slow wave sleep (SWS). Reduced SWS has been linked to hypertension in community-based studies. We sought to investigate whether SWS percentage modifies the association between OSA and prevalent hypertension. We studied 7107 patients with OSA and 1118 primary snorers who underwent in-laboratory polysomnography. Patients were classified into quartiles of percent SWS. Hypertension was defined based either on clinic blood pressure measures or on physician diagnosis. Multivariable logistic regression model showed a significant interaction effect of OSA and SWS on prevalent hypertension ( P =0.002). Decreased SWS was associated with higher odds for hypertension in OSA but not in primary snoring, with patients with OSA exhibiting <0.1% SWS (OR, 1.44 [95% CI, 1.21–1.70]; P =0.001) and those with 0.1% to 4.8% SWS (OR, 1.20 [95% CI, 1.03–1.40]; P =0.02) being more likely to have hypertension compared with those with >11.1% SWS. In analysis stratified by OSA severity, significant associations between percent SWS and blood pressure emerged only in moderate and severe OSA. Effect modifications by sex ( P =0.040) and age ( P =0.007) were also only evident in OSA, indicating that decreased SWS was associated with hypertension only in men and in patients <60 years old. Decreased SWS is associated with a dose-dependent increase in odds of prevalent hypertension in patients with OSA. The effects of SWS are likely to be modulated by OSA severity. SWS may be implicated in the heightened risk of cardiovascular diseases exhibited by patients with OSA. Abstract : Supplemental Digital Content is available in the text.